Pengaruh Reputasi Organisasi Terhadap Organizational Attractiveness Pada Perusahaan Di Sektor Perbankan Dengan Reputasi Baik Yang Mendapatkan Online Company Review Negatif Bagi Generasi Milenial - Alvyna Asijadji, Bitya; Handoyo, Seger (CV RIFAINSTITUT, 2023)
Every organization competes to increase its attractiveness in order to attract superior applicants to apply to their organization. Various factors influence the decision of prospective job applicants to apply to an organization. One of them is how the willingness of an individual to apply and work in a particular organization which is also called organizational attractiveness. Organizational reputation, which is included in one of the organizational attractiveness components, is also an influential factor in attracting quality human resources to join the organization. This study aims to determine the effect of organizational reputation on organizational attractiveness, especially in companies in the banking sector in the context of negative online company reviews. This research is a research with a quantitative approach and uses a survey method. Subjects or participants in this study are specifically the millennial generation, namely men or women aged 21 to 39 years. Participants in this study amounted to 156 participants. The analysis technique used is descriptive statistical analysis, assumption test, and correlation test.The results of this study indicate that organizational reputation has a significant effect on organizational attractiveness (p=0.000) with the value of the strength of the relationship in the moderate category (p=0.444).